2015
DOI: 10.1108/jadee-02-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Investigating demand for biofortified seeds in developing countries

Abstract: Purpose – The purpose of this paper is to explore farmer acceptance of a biofortified staple food crop in a developing country prior to its commercialization. The paper focuses on the hypothetical introduction of a high-iron pearl millet variety in Maharashtra, India, where pearl millet is among the most important staple crops. Design/methodology/approach – A choice experiment is used to investigate farmer preferences for and trade-offs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Flatbread ( bhakri ) prepared from high iron–biofortified pearl millet was rated with higher scores than that prepared from local varieties of pearl millet by Indian consumers (n = 452). 57 However, only this 1 study on the sensory acceptance of biofortified pearl millet was found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flatbread ( bhakri ) prepared from high iron–biofortified pearl millet was rated with higher scores than that prepared from local varieties of pearl millet by Indian consumers (n = 452). 57 However, only this 1 study on the sensory acceptance of biofortified pearl millet was found.…”
Section: Resultsmentioning
confidence: 99%
“…There is no effect of information on liking Consumers rated the light yellow and deep yellow cassava differentially on all sensory attributes. Study area was important factor for preference, but the deep yellow was never preferred Pearl millet Birol et al (2015) 57 India Consumers: Rural consumers, M + F, mean age: 40 y; n = 452 Sensory attributes study (5-point hedonic scale) for grain color/size, and color, taste, layers, and ease of breaking of bhakri (thick flatbread) made of HIPM or LPM Overall, HIPM was rated higher (4.2–4.9) for all attributes compared with LPM (3.5–4.2). Information (groups B and C) increased the scores for HIPM and decreased scores for LPM, except for grain color, which remained the same Consumers evaluate HIPM more favorably than LPM varieties Abbreviations : F, female; HIPM, high-iron pearl millet; IB1, iron bean 1; IB2, iron bean 2;; LPM, local pearl millet; M, male; OFSP, orange-fleshed sweet potato; PFSP, purple-fleshed sweet potato; RIB, iron biofortified red bean; SP, sweet potato; WIB, iron biofortified white bean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Birol et al. () estimated Filipino farmers’ WTP for Bt ( Bacillus thuringiensis ) maize seed, and Birol, Asare‐Marfo, Karandikar, Roy, and Diressie () investigated Indian farmers’ preferences for and trade‐offs among various production and consumption attributes of pearl millet seed with a focus on the hypothetical introduction of a high‐iron pearl millet variety. These prior studies have mostly focused on farmers’ preferences and WTP for varietal attributes or specific genetic trait of a seed to help understand farmers’ willingness to adopt a new crop variety.…”
Section: Introductionmentioning
confidence: 99%
“…Age and sex-disaggregation were fully integrated into nutrition-related aspects of HarvestPlus but gender was not as systematically considered in all aspects of the agricultural and value chain research. To better understand potential constraints to seed availability and access among target households and to inform delivery strategies, HarvestPlus conducted studies to learn from past experience with improved varieties in target countries, including pearl millet in India [27,28]; cassava in Nigeria [29] and beans in Rwanda [30].…”
Section: Delivery At Scale (≈2014-2018)mentioning
confidence: 99%